STRATEGI PEMBELAJARAN NILAI AGAMA DAN MORAL DENGAN PENDEKATAN SAINTIFIK DI TK ISLAM NURUL MUTTAQIN CAMPLONG SAMPANG - Ismail Ismail (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This study aims to analyse strategies for teaching religious and moral values (NAM) using a scientific approach at Nurul Muttaqin Islamic Kindergarten in Camplong, Sampang, and to examine the factors contributing to its success and the challenges of its implementation. This study employs a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews, and documentation, and were subsequently analysed using the Miles & Huberman model with triangulation of sources, techniques, and time to ensure the validity of the data. The results indicate that the scientific approach is effectively integrated into NAM learning through three main themes: (1) faith, through activities observing God’s creation to foster a sense of wonder and gratitude; (2) worship, through the practice of wudu and prayer framed within the scientific process; and (3) noble character, through social activities such as sharing and helping others that build empathy and honesty. Each stage of the scientific process observing, questioning, gathering information, making connections, and communicating serves as a means of naturally internalising spiritual and moral values. The success of this strategy is underpinned by three key factors: (1) the institution’s religious culture, which fosters a consistent moral and spiritual environment; (2) teachers’ creativity in integrating scientific narratives with religious values; and (3) parental support through home-school collaboration, which reinforces the continuity of children’s moral development. The challenges faced include limited experimental resources, short learning time, and variations in children’s developmental levels. Teachers overcome these challenges by utilising the local environment as a natural laboratory and implementing individual experience-based learning. This study concludes that the scientific approach is not only relevant for the cognitive development of young children but is also effective as a ta’dib (character-building) strategy that integrates faith, knowledge, and action. This model represents a holistic Islamic educational paradigm that fosters children’s spiritual, moral, and scientific awareness in a balanced manner from an early age.